2011
DOI: 10.1017/s1355617710001670
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Volume Loss, Cognitive Deficit, and Neuropsychological Performance: Comparative Measures of Brain Atrophy: II. Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) results in a variable degree of cerebral atrophy that is not always related to cognitive measures across studies. However, the use of different methods for examining atrophy may be a reason why differences exist. The purpose of this manuscript was to examine the predictive utility of seven magnetic resonance imaging (MRI)-derived brain volume or indices of atrophy for a large cohort of TBI patients (n = 65). The seven quantitative MRI (qMRI) measures included uncorrected whole brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…Volumes obtained included total white matter (WM), total gray matter (GM), total ventricular volume, and total cerebrospinal fluid space (CSF), along with total brain volume (TBV), summing for right and left hemisphere structures. Also, a ventricle-to-brain ratio (VBR) was obtained by using the FreeSurfer computation of total ventricular volume divided by TBV and multiplied by 100 to provide whole number values (Tate, Khedraki, Neeley, Ryser, & Bigler, 2011). For voxel based morphometry (VBM), the major preprocessing and analysis steps were done in SPM8 (Wellcome Trust Centre for Neuroimaging, London, UK; available at: http://www.fil.ion.ucl.ac.uk/spm) using the VBM8 toolbox (available at: http://dbm.neuro.uni-jena.de/vbm).…”
Section: Mri and Vbmmentioning
confidence: 99%
“…Volumes obtained included total white matter (WM), total gray matter (GM), total ventricular volume, and total cerebrospinal fluid space (CSF), along with total brain volume (TBV), summing for right and left hemisphere structures. Also, a ventricle-to-brain ratio (VBR) was obtained by using the FreeSurfer computation of total ventricular volume divided by TBV and multiplied by 100 to provide whole number values (Tate, Khedraki, Neeley, Ryser, & Bigler, 2011). For voxel based morphometry (VBM), the major preprocessing and analysis steps were done in SPM8 (Wellcome Trust Centre for Neuroimaging, London, UK; available at: http://www.fil.ion.ucl.ac.uk/spm) using the VBM8 toolbox (available at: http://dbm.neuro.uni-jena.de/vbm).…”
Section: Mri and Vbmmentioning
confidence: 99%
“…The ratio approach corrects for head size on an individual basis (Sanfilipo et al 2004) and has been utilized in previous studies of SH Haley et al 2007;Lane et al 2011;Opherk et al 2014). Previous research comparing this approach with other standardization techniques has revealed minimal to no differences in results, with no statistically superior standardization measure (Bigler et al 2004;Tate et al 2011). …”
Section: Neuropsychological Testingmentioning
confidence: 99%
“…Nonetheless, an enduring marker of global atrophy is a derivative of the Evans' index or ratio -the ventricle-to-brain ratio (VBR) where total ventricular volume is divided by brain volume and multiplied by 100 so that whole numbers are used in the quantification metric. The VBR is not only an established measure of overall brain integrity, but as a ratio it automatically adjusts (partially) for head size variation (Mathalon et al 1993) and commonly relates to neuropsychological status Green et al 2014;Olesen et al 2011;Tate et al 2011). Like all quantitative image techniques it is not without its drawbacks and there are circumstances where it may be best to adjust or correct for head size statistically (e.g., regression or covariance) rather than using a ratio like the VBR (Arndt et al (Arndt et al 1991).…”
Section: Overview Of Structural Neuroimaging Analysesmentioning
confidence: 99%